2012
DOI: 10.1021/jp3015436
|View full text |Cite
|
Sign up to set email alerts
|

Stacking of Hexagonal Nanocrystal Layers during Langmuir–Blodgett Deposition

Abstract: Hexagonally ordered close-packed monolayers of sterically stabilized FePt nanocrystals were deposited on substrates using the Langmuir-Blodgett technique. Monolayers of nanocrystals were also stacked by sequential Langmuir-Blodgett transfer. The structures of the nanocrystal monolayers and multilayer stacks were examined with scanning electron microscopy (SEM) and grazing-incidence small-angle scattering (GISAXS). An analytical model derived from the quasikinematic approximation provides a convenient descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
55
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(59 citation statements)
references
References 45 publications
4
55
0
Order By: Relevance
“…The spot indexing (open circles) of the GISAXS patterns corresponds to a (110) oriented bcc superlattice with a lattice constant, a bcc , of (a) 3.72 nm, (b) 6.80 nm, and (c) 11.2 nm. The solid white dots indicate the direct and reflected X-ray beam positions and the horizontal lines indicate the sample horizon (white) and the Yoneda peak for the film (red) 41. …”
mentioning
confidence: 99%
“…The spot indexing (open circles) of the GISAXS patterns corresponds to a (110) oriented bcc superlattice with a lattice constant, a bcc , of (a) 3.72 nm, (b) 6.80 nm, and (c) 11.2 nm. The solid white dots indicate the direct and reflected X-ray beam positions and the horizontal lines indicate the sample horizon (white) and the Yoneda peak for the film (red) 41. …”
mentioning
confidence: 99%
“…Alternatively, it has been shown that the most ordered and large area arrays of MNPs 3 can be assembled on water surface [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The process involves deposition of evaporative solution of MNPs on a water surface where it spreads out to form a colloidal solution film.…”
Section: Introductionmentioning
confidence: 99%
“…Providing sufficient resolution for study nano-objects they, in addition, probe large area sample surfaces due to a large beam spread resulting from a very shallow angle of incidence. Assemblies of MNPs on solid substrates were intensively studied by means of grazing incidence X-ray reflectivity (XRR) and small-angle X-ray scattering (GISAXS) 12,13,16,17,27,31,35,37,38 , neutron reflectivity (NR) and grazing incidence small-angle neutron scattering (GISANS) 17 In the present study, for the first time, to our knowledge, a unique combination of in-situ GISAXS and XRR techniques, accompanied by the pressure-area isotherm analysis, BAM and ex-situ SEM were applied for investigation of super-lattices of magnetic nano-particles as they form directly on water surface in a Langmuir trough. Size and value of the magnetic 5 …”
Section: Introductionmentioning
confidence: 99%
“…The 3D nanoparticle structures prepared by the layer‐by‐layer deposition (i.e. by repeatedly applied LB or LS technique) are characterized by a relatively high quality of the lateral order , however, their vertical correlation between the neighboring layers is rather poor . To improve it, some authors tried to fabricate the nanoparticle multilayers in the LB trough in one compression cycle by increasing the surface pressure.…”
Section: Introductionmentioning
confidence: 99%